"Living poets society" – a qualitative study of how Swedish psychologists incorporate reading and writing in clinical work. Issue 3 (2nd July 2020) - Bergqvist, Pia; Punzi, Elisabeth
ABSTRACT: Different forms of reading and writing can have therapeutic effects and therefore beneficially are incorporated into mental health care. In Swedish mental health care such incorporation is not established but the field is gaining increased interest. In this study, five psychologists in Swedish mental health care who incorporate reading and writing in their clinical work were interviewed about how they incorporate such activities and how they perceive reading and writing in terms of patient recovery. An Interpretative Phenomenological analysis resulted in the following themes: New perspectives, The psychologists' perceptions, Shared symbols, Freedom to express oneself, and Safety through structure. The results show a need for flexibility in clinical work; since unique individuals express themselves in different ways, practitioners should be encouraged to offer patients opportunities for creative expression. It is suggested that reading and writing need to be established as valid and easily identifiable interventions in Swedish mental health care.